Two arterial variations of the hand and wrist present bilaterally (persistent median artery and superficial dorsal branch of the radial artery): ultrasound findings - Belbl, Miroslav; Steyerova, Petra; Kachlik, David (Surgical and radiologic anatomy, 2024)
PURPOSE: Arterial variations of the upper limb may bear high importance for many clinical procedures, including the use of flaps in plastic surgery. We present a feasible way for visualization and confirmation of presence of these variations. METHODS: All variations were detected by ultrasonography and confirmed by Color Doppler Imaging. Proper documentation was taken in order to present our findings. RESULTS: We report a case of a 19-year-old female who showed two concomitant arterial variations of the forearm and the hand bilaterally. These two variations were the persistent median artery and the superficial dorsal branch of the radial artery which both significantly contributed to the blood supply of the hand. All examinations were performed by the same investigator and all findings were reviewed by an experienced sonographist. CONCLUSION: An unusual arrangement of the arterial system can be easily detected. We present a feasible way to prevent iatrogenic injuries and increase utilization of anatomical variants knowledge in surgery by using ultrasound prior to planning surgical procedures.
Keywords: Hand; Arm; Color; arteria radialis; zápěstí; Anatomical variation; Radial artery; mladý dospělý; ruka; Wrist; Plastic; Doppler; Young Adult; Radial Artery; ženské pohlaví; Surgical Flaps; Humans; Surgery; chirurgické laloky; Ultrasonography; Median artery; Female; lidé; paže